Pendidikan gizi terhadap pengetahuan, sikap, dan praktik sarapan pada siswa SMP IT Nurul Fajar Cikarawang - Widhi, Anisa Sekar; Alamsyah, Putri Rahmah (Program Studi Gizi, 2022)
Breakfast contributes energy by 25% of the level of total daily energy needs. One third of the students of SMP IT Nurul Fajar Cikarawang Village have poor breakfast habits and quality. Adolescence is the most important phase in the formation of an individual's eating habits. A teenager's eating habits consist of knowledge related to breakfast, one's attitudes and practices towards breakfast. Knowledge-based practices will last a long time, therefore it is important for adolescents to obtain nutrition education from various sources, one of which is school. The purpose of this study was to determine the impact of nutrition education interventions on the knowledge, attitudes, and practices of adolescents regarding breakfast. The design of this study was a quasi experimental and purposive sampling method with a sample size of 57 7th and 8th grade students aged 12-15 years at SMP IT Nurul Fajar, Cikarawang Village. The healthy breakfast nutrition education intervention was given in 2 sessions with a duration of 50 minutes for each session. The media used in this research include leaflets, posters, videos, and materials in the form of power points. The results showed that there was a significant increase in the knowledge and attitude scores of adolescents regarding healthy breakfast (pâ‰¤0.05), while the practice of breakfast in adolescents experienced an insignificant increase (p0.05). Nutrition education interventions have an impact on increasing adolescent knowledge and attitudes regarding healthy breakfast, but the impact is not seen on adolescent breakfast practices. This is because the duration and frequency of nutrition education are too short, so nutrition education interventions are needed with a longer frequency and duration.